Sealing member and method for manufacturing the same

By using γ' precipitation hardened alloy composed of elements such as Ni, Cr, Ti, Al, etc., and combining hot rolling and cold rolling processes to prepare sealing members, the problem of difficulty in maintaining sealing members functions in an environment of about 900°C is solved, and high temperature is achieved The mechanical strength and sealing properties are maintained under the slightest control of the excessive addition of Co.

CN115398015BActive Publication Date: 2025-02-11DAIDO STEEL CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202180027422.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-04-09
Filing Date
2021-04-08
Publication Date
2025-02-11
Estimated Expiration
2041-04-08

AI Technical Summary

Technical Problem

The existing sealing members are difficult to maintain their functions in a high temperature environment of around 900°C, especially because the sealing properties are reduced due to the disappearance of the γ’ phase, and the addition of Co will damage the cold rolling processability and increase costs.

Method used

Including Ni: 40% to 62%, Cr: 13% to 20%, Ti: 1.5% to 2.8%, Al: 1.0% to 2.0%, Nb: 2.0% or less, Ta: 2.0% or less, B: 0.001% was used. The γ' precipitation hardened alloy of ~0.010%, W: 3.0% or less and Mo: 2.0% or less is prepared by hot rolling and cold rolling processes to ensure that the disappearance of the γ' phase is suppressed at high temperature.

Benefits of technology

Even in an environment of about 900°C, the function of the sealing member can be maintained to ensure that the mechanical strength and sealing properties are not reduced, and at the same time, the cost and processability problems caused by excessive addition of Co are avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115398015B_ABST
    Figure CN115398015B_ABST
Patent Text Reader

Abstract

Provided is a sealing component that can maintain its function even in a use environment of about 900°C while avoiding excessive addition of Co. A sealing component comprising a γ' precipitation hardening alloy. It is characterized in that it has the following composition: in terms of mass %, it contains Ni: 40% to 62%, Cr: 13% to 20%, Ti: 1.5% to 2.8%, Al: 1.0% to 2.0% (wherein Ti / Al: 2.0 or less), Nb: 2.0% or less, Ta: 2.0% or less (wherein Nb+Ta: 0.2% to 2.0%), B: 0.001% to 0.010%, and W: 3.0% or less, Mo: 2.0% or less (wherein Mo+(1 / 2)W: 1.0% to 2.5%), and the balance is Fe and unavoidable impurities, the sealing component exhibits a hardness of 250Hv and comprises a cold rolled structure that has been cold rolled.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a sealing member including a γ' precipitation hardened cold-rolled strip and a method for producing the same, and in particular to a sealing member capable of maintaining its function even in a use environment of about 900°C and a method for producing the same. Background Art

[0002] In order to seal the joint formed by butting the pipes together so that the liquid and gas flowing inside the joint will not leak from the joint, a metal sealing member is inserted into the joint. For example, the pipes of a turbocharger combined with a reciprocating engine are used at a high temperature of about 700°C to 800°C, so such sealing members use precipitation hardening Ni-based and Ni-Fe-based heat-resistant alloys with excellent high-temperature strength such as Inconel718 (trade name) and Nimonic263 (trade name).

[0003] For example, Patent Document 1 discloses an Fe-Ni-Cr alloy for exhaust valves of automobile engines, etc., which can maintain high strength even when exposed to 800°C for a long time while reducing the amount of Ni. The alloy has a composition in which Ni: 30% to 62%, Cr: 13% to 20%, etc. are added to Fe by mass%, and after solution treatment at 1050°C, aging treatment is performed at 750°C. By reducing the amount of Ni, the γ' phase, which is a precipitated phase that imparts high temperature strength, becomes unstable, but this can be avoided by adjusting the amount of Ti.

[0004] In addition, reference 2 discloses a method for manufacturing a heat-resistant component, wherein an alloy having a component composition in which Ni: 30% to 45%, Cr: 10% to 25%, Ti, Al, etc. are added to Fe in mass % and the atomic ratio of Ti / Al is adjusted is processed into a component after cold working or warm working, and aging treatment is performed in a state where the working strain remains. The heat-resistant component can suppress the precipitation of η phase, which is a brittle phase, even if it is exposed to 800°C or above for a long time by adjusting the atomic ratio of Ti / Al, and the mechanical strength does not decrease.

[0005] If it is a heat-resistant alloy as described above, sufficient sealing performance as a sealing member can be expected. Furthermore, for sealing members for automobile engines such as exhaust gaskets, since heating and cooling from room temperature to high temperature during use are repeatedly applied, it is also necessary to have excellent resistance to permanent strain like a "spring".

[0006] For example, cited document 3 discloses a Fe-Ni-Cr alloy for heat-resistant springs, which has a composition of 20% to 45% Ni and 10% to 25% Cr added to Fe in mass %, and can be used at about 500°C to 600°C. In the spring manufacturing process, the alloy is subjected to cold working such as cold rolling and cold drawing, and then aging treatment is performed. Here, it is described that in order to improve the permanent strain resistance, it is necessary to increase the amount of elements forming the γ' phase, optimize the atomic % ratio of Ti to Al, add B, and add solid solution strengthening elements such as Mo and W.

[0007] Prior art literature

[0008] Patent Literature

[0009] Patent Document 1: Japanese Patent Application Publication No. 2004-277860

[0010] Patent Document 2: Japanese Patent Application Laid-Open No. 11-117019

[0011] Patent Document 3: Japanese Patent Application Publication No. 2005-002451 Summary of the invention

[0012] Problem that the invention aims to solve

[0013] Regarding sealing components, in recent years, as the performance of turbochargers has improved, they are required to be used at higher temperatures than before, around 900°C. In contrast, in the above-mentioned general Ni-based alloys, generally speaking, the γ" phase and γ' phase of the precipitated phase that impart high-temperature strength above 800°C change to the δ phase that does not contribute to high-temperature strength, and the sealing performance is easily reduced. In addition, sometimes the γ' phase disappears at around 900°C, in which case the sealing performance is also reduced. On the other hand, it is possible to consider adding Co as an element to improve high-temperature strength, but this will impair the processability of cold rolling used as a sealing component, and it is also poor in terms of cost.

[0014] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a sealing member including a cold-rolled strip that can maintain its function even in a use environment of about 900° C. while avoiding excessive addition of Co.

[0015] Solutions for solving problems

[0016] The sealing member of the present invention is characterized in that it is a sealing member comprising a γ' precipitation hardening alloy, and the sealing member has the following composition: in terms of mass %, it contains Ni: 40% to 62%, Cr: 13% to 20%, Ti: 1.5% to 2.8%, Al: 1.0% to 2.0% (wherein Ti / Al: 2.0 or less), Nb: 2.0% or less, Ta: 2.0% or less (wherein Nb+Ta: 0.2% to 2.0%), B: 0. 001%~0.010%, W: 3.0% or less, and Mo: 2.0% or less (wherein, Mo+(1 / 2)W: 1.0%~2.5%), and can arbitrarily contain C: 0.08% or less, Si: 1.0% or less, Mn: 1.0% or less, P: 0.02% or less, S: 0.01% or less, the balance being Fe and unavoidable impurities, the sealing component presents a hardness of more than 250Hv and includes a cold rolled structure that has been cold rolled.

[0017] According to this feature, even when used for a long time at high temperature, the disappearance of fine precipitates including the γ' phase can be suppressed, and the function as a sealing member can be maintained even in a use environment of about 900°C.

[0018] In the above invention, the metal structure may be characterized by having fine precipitates containing a γ' phase dispersed in the grains. According to this feature, strengthening by the γ' phase is obtained in advance, and the function as a sealing member can be maintained even in a use environment of about 900°C.

[0019] In the above invention, it may be characterized in that 5% or less of the Ni is replaced with Co. According to this feature, the creep strength is improved and the function as a sealing member can be maintained even in a use environment of about 900°C.

[0020] In the above invention, the feature may be that Cu: 0.1% to 3.0% is further contained. According to this feature, the cold workability and oxidation resistance are improved, and the function as a sealing member can be maintained even in a use environment of about 900°C.

[0021] In the above invention, the cold-rolled structure may include 0.05% or more of inhomogeneous strain. According to this feature, the function as a sealing member can be maintained even in a use environment of about 900°C.

[0022] In the above invention, it may be characterized in that after the cold rolled structure is heated at 900°C for 400 hours, the area ratio of non-recrystallized grains containing γ' phase in the grains in the observed cross section is maintained at 30% or more. According to this feature, even if used at 900°C for 400 hours, the disappearance of fine precipitates containing γ' phase can be further suppressed, and the function as a sealing member can be maintained.

[0023] In addition, the manufacturing method of the sealing component of the present invention is characterized in that it is a manufacturing method of the sealing component based on a cold-rolled strip containing a γ' precipitation hardening alloy, and the manufacturing method includes the following steps: a hot rolling step, processing an alloy having the following component composition: containing Ni: 40% to 62%, Cr: 13% to 20%, Ti: 1.5% to 2.8%, Al: 1.0% to 2.0% (wherein Ti / Al: 2.0 or less), Nb: 2.0% or less, Ta: 2.0% or less (wherein, Nb+Ta: 0.2%~2.0%), B: 0.001%~0.010%, and W: 3.0% or less, Mo: 2.0% or less (wherein, Mo+(1 / 2)W: 1.0%~2.5%), and can arbitrarily contain C: 0.08% or less, Si: 1.0% or less, Mn: 1.0% or less, P: 0.02% or less, S: 0.01% or less, the balance being Fe and unavoidable impurities; and a cold rolling process to impart cold rolling strain to exhibit a hardness of 250Hv or more.

[0024] According to this feature, it is possible to obtain a sealing member which can suppress the disappearance of fine precipitates including the γ' phase even when used for a long time at high temperature and can maintain its function even in a use environment of about 900°C.

[0025] In the above invention, it is also possible that the hot rolling step or the cold rolling step is a step of imparting a metallographic structure in which fine precipitates containing a γ' phase are dispersed in the grains. According to this feature, a sealing member that has been strengthened in advance by the γ' phase and can maintain its function as a sealing member even in a use environment of about 900°C can be obtained.

[0026] In the above invention, it may be characterized in that 5% or less of the Ni is replaced with Co. According to this feature, a sealing member having improved creep strength and capable of maintaining a function as a sealing member even in a use environment of about 900°C can be obtained.

[0027] In the above invention, the feature may be that Cu: 0.1% to 3.0% is further contained. According to this feature, a sealing member can be obtained which can maintain the function as a sealing member even in a use environment of about 900°C while improving cold workability and oxidation resistance.

[0028] In the above invention, the cold rolling step may be a step of imparting a cold rolled structure including 0.05% or more of non-uniform strain. According to this feature, a sealing member capable of maintaining its function as a sealing member even in a use environment of about 900°C can be obtained.

[0029] In the above invention, it may be characterized in that the cold rolling step is a step of imparting a cold rolled structure, and the cold rolled structure maintains the area ratio of non-recrystallized grains containing γ' phase in the grains at 30% or more in the observed cross section after heating at 900°C for 400 hours. According to this feature, it is possible to obtain a sealing member that can further suppress the disappearance of fine precipitates containing γ' phase even when used at 900°C for 400 hours and maintain the function as a sealing member. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 1 is a flowchart showing a method for manufacturing a sealing member in one embodiment of the present invention.

[0031] Figure 2 This is a cross-sectional structural photograph of a cold-rolled strip for a sealing member, with the vertical direction of the paper plane being the compression direction.

[0032] Figure 3 This is a cross-sectional microstructure photograph of the steel after cold rolling and annealing and aging treatment.

[0033] Figure 4 This is a schematic diagram showing the cross-sectional structure of an alloy when used at high temperature for a long time.

[0034] Figure 5 This is a table showing the composition of ingredients of Examples and Comparative Examples related to production tests.

[0035] Figure 6 This is a list of values ​​of conditional expressions related to the component compositions of Examples and Comparative Examples.

[0036] Figure 7 This is a table showing the cold rolling rates and test results of Examples and Comparative Examples.

[0037] Figure 8 This is a photograph of the cross-sectional structure after the heating test of Example 1.

[0038] Fig. 9 This is a photograph of the cross-sectional structure of Comparative Example 1 after the heating test. DETAILED DESCRIPTION

[0039] use Figure 1 to Figure 3 A sealing member and a method for producing the same as one embodiment of the present invention will be described.

[0040] The sealing component of the present embodiment is obtained by a Fe-Ni-Cr alloy having the following composition: in mass %, it contains Ni: 40% to 62%, Cr: 13% to 20%, Ti: 1.5% to 2.8%, Al: 1.0% to 2.0% (including Ti / Al: less than 2.0), Nb: less than 2.0%, Ta: less than 2.0% (including Nb+Ta: 0.2% to 2.0%), B: 0.001% to 0.010%, W: less than 3.0%, and Mo: less than 2.0% (including Mo+(1 / 2)W: 1.0% to 2.5%), and can arbitrarily contain C: less than 0.08%, Si: less than 1.0%, Mn: less than 1.0%, P: less than 0.02%, S: less than 0.01%, and the balance is substantially Fe.

[0041] like Figure 1 As shown, the Fe-Ni-Cr alloy is made into a slab or a steel billet by hot forging, and then formed into a desired shape by hot rolling (hot rolling: S1). Then, it is formed into a cold-rolled strip for a sealing member, which is a raw material of the sealing member, by cold rolling, so as to present a hardness of more than 250Hv (cold rolling: S2). By obtaining this hardness, the shape of the flange can be maintained when it is fastened as a sealing member, and the sealing performance can be ensured. It should be noted that the hardness is also preferably set to less than 420Hv to prevent the cracking of the sealing member obtained thereby during fastening.

[0042] In the cold rolling (S2), it is preferred to perform rolling in multiple times, and perform annealing between each rolling. Thus, a γ' precipitation hardened cold-rolled strip for sealing components can be obtained. In other words, the cold-rolled strip for sealing components is obtained by cold rolling as the final process, and no heat treatment after cold rolling is required when the sealing components are obtained. It should be noted that the thickness of the cold-rolled strip for sealing components is in the range of 0.05 mm to 0.5 mm, preferably in the range of 0.1 mm to 0.3 mm.

[0043] Here, if Figure 2 As shown, the cold-rolled strip for sealing member obtained in this way presents the hardness of above 250Hv and has a cold-rolled structure after cold rolling. In particular, the grains are arranged in a manner that the length direction is toward the rolling direction (the left and right direction of the paper). It is believed that such a rolling structure can also contribute to the maintenance of mechanical strength at high temperature.

[0044] The cold-rolled strip for sealing members may be manufactured to have a cold-rolled structure obtained by cold rolling with fine precipitates including a γ' phase dispersed in crystal grains, but fine precipitates including a γ' phase may not be dispersed in crystal grains.

[0045] In the former case, for example, it is sufficient to make the temperature of the heating in hot rolling (S1) or the annealing in cold rolling (S2) higher than the solvus temperature of the γ' phase. Furthermore, it is preferred that the cooling rate after these heatings is set to 1°C / s to 50°C / s and cooled to 800°C, and under this cooling condition, a cold-rolled structure in which fine precipitates containing the γ' phase are dispersed in the grains is efficiently obtained. It should be noted that the cooling condition below 800°C can be appropriately set. In addition, the precipitation of the γ' phase is not limited to either hot rolling (S1) or cold rolling (S2), and the γ' phase can also be precipitated in two times.

[0046] In the latter case, by using in an environment of 800°C or higher, a metallographic structure in which fine precipitates including a γ' phase are dispersed in crystal grains is immediately obtained, and the function required as a sealing member can be maintained even in an environment of about 900°C.

[0047] It should be noted that if Figure 3 As shown, it can be seen that when annealing and aging treatment are performed after cold rolling, the grains have no directionality and the cold rolled structure disappears. In other words, such heat treatment is not necessary after cold rolling.

[0048] Next, the sealing member is cut with a cold-rolled strip by a known method and processed into the shape of the sealing member (cutting and processing: S3). As mentioned above, the sealing member is not heat-treated before and after cutting and processing (S3), and is directly used as the sealing member with the cold-rolled structure obtained by cold rolling (S2).

[0049] According to the sealing member as described above, even when used as a sealing member at high temperature for a long period of time, the disappearance of fine precipitates including the γ' phase can be suppressed, and the function required as a sealing member can be maintained even in a use environment of about 900°C, for example.

[0050] However, if Figure 4 As shown, in a γ' precipitation hardening alloy in which fine precipitates containing γ' phase (hereinafter referred to as γ' grains 11) are dispersed, during use at high temperature, the γ' grains 11 are sometimes transformed into η phase or δ phase 21 accompanied by recrystallization, and recrystallized grains 20 containing η phase or δ phase 21 are generated. The γ' grains 11 are particularly necessary to maintain high mechanical strength at high temperature, but the mechanical strength is reduced by their disappearance. Therefore, as a sealing member, it is preferred that a large number of unrecrystallized grains 10 remain, and the unrecrystallized grains 10 are grains that will not recrystallize and maintain γ' grains even if used for a long time at high temperature. This can be confirmed by a heating test, for example, after a heating test at 900°C for 400 hours, the area ratio of the unrecrystallized grains 10 containing the γ' phase in the grains is measured in the observed cross section. After the heating test, it is preferred to maintain the area ratio of the unrecrystallized grains 10 at 30% or more.

[0051] In addition, the cold-rolled structure of the cold-rolled strip for sealing components obtained by cold rolling preferably contains more than 0.05% of non-uniform strain, and more preferably the non-uniform strain is set to 0.05% to 0.33%. Thus, the hardness and the like as required for the sealing component can be reliably obtained. It should be noted that the non-uniform strain is measured by the Williamson-Hall method as follows. That is, a 10mm×10mm test piece is collected from the cold-rolled strip for sealing components, and the strain layer formed by mechanical grinding is removed by electrolytic grinding on the basis of mechanical grinding from the surface, so that the plate thickness is 1 / 2 of the original plate thickness. In this test piece, an X-ray diffraction device equipped with a Co bulb is used for XRD measurement, and the half-value width of the diffraction peaks of (111) (200) (220) (311) and (222) planes is obtained using the commercially available XRD analysis software "JADE 9.6". After correcting the strain using the half-value width of the unstrained Si sample, a Williamson-Hall plot was prepared, and the inhomogeneous strain ε was calculated from its slope.

[0052] The total reduction ratio by cold rolling (cold rolling ratio) is preferably 10% or more, and more preferably within a range of 10% to 40%. This makes it easy to obtain the above-mentioned non-uniform strain.

[0053] It should be noted that in the above composition, it is also possible to set a composition in which 5% by mass or less of Ni is replaced with Co. By adding Co, creep strength can be improved. In addition, in the above composition, it is also possible to set a composition further containing Cu in the range of 0.1% by mass to 3.0% by mass. By adding Cu, cold workability and oxidation resistance can be improved.

[0054] [Manufacturing test]

[0055] Next, use Figures 5 to 9 The results of actually manufacturing cold-rolled strips and investigating the non-uniform strain relative to the rolling rate, room temperature hardness, area ratio of non-recrystallized grains and high temperature hardness are described. It should be noted that the cold-rolled strip for sealing members is made into sealing members without heat treatment as described above, so the sealing members can be evaluated.

[0056] First, use Figure 5 and Figure 6 The alloys of the respective component compositions shown in Examples 1 to 6 and Comparative Examples 1 to 3 were prepared in the same manner as described above to obtain cold rolled strips. Figure 6 The use is shown in mass % Figure 5 The calculation results of the conditional formula for the numerical values ​​when the contents of the elements in the composition are shown.

[0057] like Figure 7 As shown, for the obtained cold-rolled strip, the non-uniform strain, room temperature hardness, area ratio of non-recrystallized grains, and high temperature hardness at 900°C are measured and recorded respectively. As a sealing component, the hardness at room temperature needs to be set to 250Hv or more. In addition, it is necessary to leave non-recrystallized grains after a heating test at 900°C × 400 hours. Here, the case where the room temperature hardness is set to 250Hv or more, and the area ratio of non-recrystallized grains after the heating test is set to 20% or more is judged as passed and recorded as "△", the case where it is set to 30% or more is judged as good and recorded as "0", and the other cases are judged as unsuccessful and recorded as "×".

[0058] In Examples 1 to 6, the room temperature hardness of the obtained cold-rolled strips was 250 Hv or more, and the area ratio of the unrecrystallized grains after the heating test was 20% or more, which was judged as good or qualified. In addition, the room temperature hardness was within the preferred range of 420 Hv or less, and the non-uniform strain was also within the preferred range of 0.05% or more. As for the high temperature hardness, it was stable at a relatively high value of 170 Hv to 230 Hv.

[0059] Refer to Figure 8 It is found that in the cross-sectional structure after the heating test of Example 1, non-recrystallized grains in which γ' phase particles remain are arranged over a wide range in the cross section.

[0060] It should be noted that the area ratio of the unrecrystallized grains in Example 6 is just 20% which is judged as passing, which is somewhat different from Examples 1 to 5 which are judged as good and have a value of more than 30%. In addition, in the non-uniform strain, Examples 1 to 5 are set in a more preferred range of 0.05% to 0.33%, while Example 6 is set to 0.35% which is larger than that. That is, compared with Example 6, the area ratio of the unrecrystallized grains and the non-uniform strain of Examples 1 to 5 are in a more preferred range, and it is believed that the reason is due to the rolling rate of cold rolling. In Example 6, the cold rolling rate is set to 50% which is larger than that of other Examples, but it is believed that this increases the non-uniform strain, and promotes the change from the γ' phase to the η phase and recrystallization in the heating test. That is, in the cold rolling rate, 10% to 40% including Examples 1 to 5 is set as the preferred range.

[0061] On the other hand, in Comparative Example 1, the area ratio of the non-recrystallized grains after the heating test was reduced to 5%, and the high temperature hardness was also 120 Hv, which was significantly reduced compared with the example. As a result, it was judged as unsatisfactory. It is believed that since the Ti / Al value exceeded 2.0, the γ' phase was unstable and the non-recrystallized grains could not be fully maintained after the heating test.

[0062] Refer to Fig. 9It is found that in the cross-sectional structure after the heating test of Comparative Example 1, only a few unrecrystallized grains remain, the unrecrystallized grains contain γ' phase particles, and recrystallized grains containing η phase are widely arranged.

[0063] In Comparative Example 2, almost no unrecrystallized grains remained after the heating test, and the area ratio was set to 0%, and the high temperature hardness was 110 Hv, which was significantly lower than that of the embodiment. As a result, it was judged as unsatisfactory. It is believed that although the amount of Mo was increased instead of reducing the content of Ti and Al as γ' generating elements to obtain room temperature hardness, the generation of γ' phase particles was reduced, so the unrecrystallized grains after the heating test could not be maintained.

[0064] In Comparative Example 3, almost no unrecrystallized grains remained after the heating test, and the area ratio was set to 0%, and the high temperature hardness was 130 Hv, which was significantly lower than that of the embodiment. As a result, it was judged as unsatisfactory. It is believed that the content of Al as a γ' generating element is small, the value of Ti / Al also exceeds 2.0, making the γ' phase unstable, and the presence of a large amount of C causes recrystallization, so it is impossible to maintain the unrecrystallized grains after the heating test.

[0065] As described above, while Comparative Examples 1 to 3 were judged as unsatisfactory, Examples 1 to 5 were judged as good, and Example 6 was judged as passing, the room temperature hardness was set to 250 Hv or more, so that a relatively large number of non-recrystallized grains remained after the heating test. That is, a cold-rolled strip for a sealing member capable of maintaining mechanical strength at high temperatures can be obtained, and thus a sealing member capable of maintaining mechanical strength at high temperatures can be obtained in the same manner.

[0066] Incidentally, the composition range of the cold-rolled strip for sealing member that can be judged as good or pass including the above-mentioned examples and the alloy that can impart mechanical properties substantially equivalent to those of the sealing member is determined as follows.

[0067] Ni is an element required to make the matrix austenite to improve heat resistance and corrosion resistance, generate γ' phase as precipitation strengthening phase, and obtain phase stability and mechanical strength to ensure hot workability. On the other hand, excessive content leads to increased costs. Considering these, Ni is in the range of 40% to 62% by mass, preferably in the range of 40% to 54%, and more preferably in the range of 45% to 54%.

[0068] Cr is an element necessary for ensuring heat resistance. On the other hand, when contained in excessive amounts, σ ​​phase is precipitated to gradually reduce toughness and reduce mechanical strength at high temperatures. Considering these, Cr is within the range of 13% to 20% by mass, preferably within the range of 13% to 18%.

[0069] Ti, together with Al, Nb, and Ta, combines with Ni to form a γ' phase that is effective for improving mechanical strength at high temperatures. It is an element required to maintain the solid solution temperature of the γ' phase at a high level. On the other hand, when contained in excessive amounts, workability is reduced, and in addition, η phase (Ni3(Ti, Nb)) is easily precipitated, reducing mechanical strength at high temperatures. Considering these, Ti is within the range of 1.5% to 2.8% by mass.

[0070] Al is an element necessary for bonding with Ni to form a γ' phase and thereby ensuring mechanical strength at high temperatures, but when contained in excess, hot workability is reduced. In consideration of these factors, the content of Al is within a range of 1.0% to 2.0% by mass.

[0071] Here, Ti / Al controls the phase stability of the γ' phase that becomes fine precipitates for precipitation hardening. This phase stability is achieved when it is 2.0 or less, but if it exceeds 2.0, it induces precipitation of the η phase. Therefore, Ti / Al is 2.0 or less.

[0072] Nb is a forming element of the γ' phase, and has the effect of promoting the hardening brought by the γ' phase. On the other hand, when it is contained in excess, it is easy to precipitate the η phase (Ni3(Ti, Nb)), which reduces the mechanical strength at high temperatures. In addition, Ta is also a forming element of the γ' phase, and has the effect of promoting the hardening brought by the γ' phase. On the other hand, when it is contained in excess, it is easy to precipitate the η phase (Ni3(Ti, Ta)), which also reduces the mechanical strength at high temperatures. Taking these into consideration, in terms of mass %, Nb is within the range of 2.0% or less, and Ta is within the range of 2.0% or less. Among them, Nb+Ta is within the range of 0.2% to 2.0%.

[0073] B is an element that helps improve hot workability and inhibits the formation of η phase to prevent the decrease of mechanical strength and toughness at high temperature, thereby improving high temperature creep strength. On the other hand, when contained in excessive amount, the melting point of the alloy is lowered and the hot workability is deteriorated. Considering these, B is in the range of 0.001% to 0.010% by mass%.

[0074] W and Mo are elements necessary for strengthening the matrix by solid solution to improve mechanical strength at high temperatures. On the other hand, excessive inclusion leads to increased costs and reduced workability. Considering these, W is within the range of 3.0% or less, Mo is within the range of 2.0% or less, and Mo+(1 / 2)W is within the range of 1.0% to 2.5% by mass%.

[0075] C is an element that combines with Cr, Ti, Nb, and Ta to form carbides, thereby effectively improving mechanical strength at high temperatures, and can be added arbitrarily. On the other hand, when excessively contained, in addition to excessively generating carbides and damaging hot workability, cold workability, toughness, and ductility, it also induces recrystallization starting from carbides, reducing mechanical strength at high temperatures. Taking these into consideration, C is within the range of 0.08% or less in mass %.

[0076] Si is an element that mainly functions as a deoxidizer during solution refining and can be added arbitrarily. On the other hand, when contained in excessive amounts, toughness is reduced and workability is impaired. In consideration of these, Si is within a range of 1.0% or less in mass %.

[0077] Mn is an element that functions as a deoxidizer like Si and can be added arbitrarily. On the other hand, if it is contained in excessive amount, workability and oxidation resistance at high temperature are impaired. In consideration of these, Mn is within the range of 1.0% or less in mass %.

[0078] P and S are impurities that are inevitably contained and reduce hot workability. Therefore, in terms of mass %, P is within the range of 0.02% or less, and S is within the range of 0.01% or less.

[0079] Co is effective for improving creep strength at high temperatures. On the other hand, excessive inclusion not only increases costs but also reduces the phase stability of the γ' phase. In consideration of these, Co can be included in a range of 5% or less by mass to replace a portion of Ni.

[0080] Cu is also effective in improving cold workability and oxidation resistance, and can be added arbitrarily. On the other hand, excessive content reduces hot workability. Considering these, Cu can be added arbitrarily in the range of 0.1% to 3.0% by mass.

[0081] Although representative embodiments of the present invention have been described above, the present invention is not necessarily limited thereto, and a person skilled in the art will be able to find various alternative embodiments and modifications without departing from the spirit of the present invention or the scope of the appended claims.

[0082] Description of Reference Numerals

[0083] 10. Unrecrystallized grains

[0084] 11. γ' grains (fine precipitates containing γ' phase)

[0085] 20. Recrystallized grains

[0086] 21. η phase or δ phase

Claims

1. A sealing member, characterized in that: The sealing member is a γ' precipitation hardening alloy having the following composition: composition: Contains by mass% Ni: 40% to 62%, Cr:13%~20%, Ti: 1.5%~2.8%, Al: 1.0% to 2.0%, of which Ti / Al: 2.0 or less, Nb: 2.0% or less, Ta: 2.0% or less, of which Nb+Ta: 0.2% to 2.0%, B: 0.001% to 0.010%, and W: 3.0% or less, Mo: 2.0% or less, of which Mo+(1 / 2)W: 1.0% to 2.5%, and Can contain any C: 0.08% or less, Si: 1.0% or less, Mn: 1.0% or less, P: 0.02% or less, S: 0.01% or less, The balance is Fe and unavoidable impurities. The sealing member has a hardness of 250 Hv or more and includes a cold-rolled structure. After the cold rolled structure is heated at 900° C. for 400 hours, the area ratio of non-recrystallized grains containing the γ' phase in the grains in the observed cross section is maintained at 30% or more. The sealing member has a metallographic structure in which fine precipitates including a γ' phase are dispersed in crystal grains. The cold-rolled structure includes 0.05% or more of non-uniform strain.

2. The sealing member according to claim 1, characterized in that Less than 5% of the Ni content is replaced with Co.

3. The sealing member according to claim 1 or 2, characterized in that: It also contains Cu: 0.1% to 3.0%.

4. A method for manufacturing a sealing member, characterized in that: The invention discloses a method for manufacturing a sealing member made of a γ' precipitation hardening alloy, the method comprising the following steps: Hot rolling process, processing alloys with the following composition: Contains by mass% Ni: 40% to 62%, Cr:13%~20%, Ti: 1.5%~2.8%, Al: 1.0% to 2.0%, of which Ti / Al: 2.0 or less, Nb: 2.0% or less, Ta: 2.0% or less, of which Nb+Ta: 0.2% to 2.0%, B: 0.001% to 0.010%, and W: 3.0% or less, Mo: 2.0% or less, of which Mo+(1 / 2)W: 1.0% to 2.5%, and Can contain any C: 0.08% or less, Si: 1.0% or less, Mn: 1.0% or less, P: 0.02% or less, S: 0.01% or less, The balance is Fe and unavoidable impurities; and The cold rolling process imparts cold rolling strain to achieve a hardness of more than 250Hv. The hot rolling step or the cold rolling step is a step of providing a metallographic structure in which fine precipitates including a γ' phase are dispersed in the grains. The cold rolling step is a step of providing a cold rolled structure in which the area ratio of non-recrystallized grains containing a γ' phase in the grains is maintained at 30% or more in an observed cross section after heating at 900°C for 400 hours. The cold rolling step is a step of providing a cold rolled structure including a non-uniform strain of 0.05% or more.

5. The method for manufacturing a sealing member according to claim 4, characterized in that: Less than 5% of the Ni content is replaced with Co.

6. The method for manufacturing a sealing member according to claim 4 or 5, characterized in that: It also contains Cu: 0.1% to 3.0%.

Citation Information

Patent Citations

  • Production of heat resistant parts

    JP1999117019A

  • Heat-resistant alloy for high-strength exhaust valve excellent in overaging resistance

    JP2004277860A

  • Fe-Ni-Cr ALLOY FOR HEAT-RESISTANT SPRING AND PRODUCTION METHOD OF HEAT-RESISTANT SPRING

    JP2005002451A

  • Heat resistant alloy excellent in cold workability and overaging characteristic

    JP1998130790A

  • High-strength, heat-resistant alloy for exhaust valves with improved overaging-resistance

    US20040184946A1